Detection Accuracy of [68Ga] PSMA PET/CT with Rising PSA in Prostate Cancer - Mohan, Parul; Wadhwa, Palak; Mahajan, Harsh; Kumar, Dileep; Aringhieri, Giacomo; Cioni, Dania (World Journal of Nuclear Medicine, 2025)
Objective The objective of this study was to evaluate the clinical utility of gallium-68 [68Ga] prostate-specific membrane antigen (PSMA) positron emission tomography/computed tomography (PET/CT) with rising prostate-specific antigen (PSA) levels in prostate cancer diagnosis.Methods This is a retrospective, single-center, observational cross-sectional study, which is provided after ethics committee clearance, from May 2, 2022 to June 25, 2022. Study includes sample size of 50 patients with prostate adenocarcinoma with varying PSA levels and Gleason score of 6 to 9 who underwent [68Ga] PSMA PET/CT scan. The patients included in this study underwent PET/CT scan on uMI550 (United Imaging Healthcare, Shanghai, China).Results All patients were divided into three groups based on PSA levels in ng/mL as: PSA ≤ 0.2 (8%), 0.2 < PSA ≤ 1 (10%), 1 < PSA ≤ 3 (8%), 3 < PSA ≤ 10 (18%), and PSA > 10 (56%). Among 50 scans, at least one PSMA avid lesion was visualized in 41 scans (78.9%). These scans were considered positive and included in this study, rest of the scans had insignificant PSMA uptake and were considered negative. [68Ga] PSMA PET/CT detection rates were 75.0, 20.0, 50.0, 88.90, and 89.3% in patients with PSA ≤ 0.2, 0.2 < PSA ≤ 1, 1 < PSA ≤ 3, 3 < PSA ≤ 10, and PSA > 10, respectively. In addition to prostate bed, lesions were also visualized in lymph nodes (32%), liver (2%), skeleton (28%), and thorax (6%). Considering lesions in the prostate bed a significant direct correlation was detected between maximal standardized uptake value (SUVmax) and PSA value (p = 0.03).Discussion PSMA PET/CT has been demonstrated to be an effective method for identifying both low-grade Gleason score tumors and low PSA levels. The study provides support for the use of [68Ga] PSMA PET/CT in conjunction with PSA levels for the evaluation of prostate cancer, including local recurrence and distant metastases.Conclusion The findings of this study indicate that PSMA PET/CT is an effective method for diagnosing prostate cancer, as it allows for the detection of high SUVmax values in pathological tissues. Furthermore, high sensitivity and detection rates are noted with PSMA PET/CT scan even in cases where PSA levels were low. Therefore, this study demonstrates that [68Ga] PSMA PET/CT is beneficial for the early detection of prostate cancer and the prediction of treatment outcomes.
Keywords: PSA; PSMA PET/CT; digital PET/CT scanner; prostate cancer; prostate-specific antigen; molecular imaging; biomarkers